A PROCESS OF TERRITORIALIZATION IN THE NEW URBAN HABITAT ZONE OF SERKINA: THE CASE OF COLLECTIVE SOCIAL HOUSING - Oualid Bencheikh Lehocine,; Toufik Khenchoul,; Assia Lifa, (International Journal of Innovative Technologies in Social Science, 2024)
The Serkina new urban habitat zone (ZHUN Serkina) is one of the four new housing zones in the city of Constantine. In our article, we will try to focus on the territorial integration (socio-spatial integration) of the inhabitants of this ZHUN, by favoring a ‘bottom-up’ approach, which pay the main attention to the experiences of the inhabitants and their degree of territorialization. The study based on observation technique and a questionnaire survey of a sample of 109 households. In other words, we will try to clarify each individual's ability to forge specific relationships with the space in which are lived.